Teacher Creativity as Correlate to English Essay Writing Achievement of Students with Learning Disabilities in Ibadan, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2026)
Students with Learning disabilities are a unique minority in regular school setting in Nigeria, as such they often obstructed by partial or total delay in one aspect of learning development or the other. This paper discusses the impact of English language of teacher creativity on students with learning disabilities achievement in essay writing in Oyo State Nigeria.  Multistage sampling technique was used to select seven government owned schools in seven towns within Ibadan, Nigeria. Eighteen (18) English Language subject teachers in Junior Secondary Schools II were enumerated while seven (7) intact classes of Juniors Secondary School II of students with learning disabilities totaling five hundred and eighty-five (585) were purposively selected for research purpose through nomination by the class teachers based on the academic records of each student in their classes across the seven schools.  Two validated research instruments were used: Teacher Creativity Rating Scale (r=0.83); Essay Writing Achievement Test (r=0.72). Two research questions were raised and answered. The findings revealed that teacher creativity has a great influence on students’ achievement in essay writing. The researcher then recommended that teacher of English language courses should make use of creative skills effectively during teaching/learning process, most especially in essay writing.